DISPUTE SETTLEMENT OF ANTI-DUMPING LEGAL ASPECT IN INDONESIA BASED ON GATT/WTO PROVISIONS (ALLEGATIONS CASE STUDY OF DUMPING WOOD FREE COPY PAPER BETWEEN SOUTH KOREA AND INDONESIA) - Idha Mutiara Sari (Lampung Journal of International Law, 2020)
The increase of trading activities in economic globalization requires a strong international financial and trade system to distribute capital in the implementation of world trade. From the considerable problems in the globalization of trade, the international community has begun to draft several regulations that can be agreed together. Therefore, there is a need for rules and regulations in international trade relations, in this case, an agreement realizing the role of GATT/WTO as an international trade organization that determines and assists in resolving trade disputes between countries. Legal issues will be discussed in this paper is, 1) How is the implementation of GATT / WTO about anti-dumping law; 2) How is the implementation of anti-dumping law in Indonesia; 3) What is the legal aspect of dispute resolution of the case study in the alleged Dumping Wood Free Copy Paper case between South Korea and Indonesia. In this paper, the research method is normative legal research that accommodates regulations, decisions and general principles of (international-trade) law.The results discussed in this paper are the role of GATT/WTO in dealing with anti-dumping in Indonesia regulation and implementation of anti-dumping in its legal territorial area, and South Korea’s anti-dumping case study on Indonesia. Conclusions from this paper include, Indonesia must better to protect a regulation regarding anti-dumping measures by enforcing strong laws and other anti-dumping regulations. It is a legal urgency as an export-import activity because in the implementation of international trade defence is not enough if a Government Decree regulates anti-dumping actions. Still, it must continue to update the rules of the WTO’s provisions which always develop.